Meta 19 do PNE: o cenário brasileiro da gestão democrática escolar nos planos estaduais e distrital de educação - CARVALHO, Janaína Brito (UNIFAP – Universidade Federal do Amapá, 2022)
The object of this study is democratic school management and its implementation process in the Brazilian scenario through goal 19 of the National Education Plan, Law no. 13.005 / 2014, where the research had the following guiding question: how has the achievement of goal 19 of the National Education Plan been developed in the Brazilian State and District Education Plans, considering the current democratic context of struggles and resistance in the country? The general objective was to analyze how the achievement of goal 19 of the National Education Plan in the Brazilian State and District Education Plans has been developed, considering the current democratic context of struggles and resistance in the country. Regarding the theoretical and methodological frameworks adopted, documental research was chosen, with a quantitative and qualitative approach (SANTOS FILHO In GAMBOA, 2013) in the State and District Education Plans of the twenty-seven Brazilian federated entities. The analytical process of the information was based on the assumptions of the Content Analysis, observing the complexities of the messages expressed by the official documents, the focus of the investigation. For theoretical support, it was based on Historical Dialectical Materialism, because it is understood that it explains reality from the historical and social circumstances, establishing relationships in the totalizing concreteness and in the studied phenomenon. Thus, through the analysis, the regulation of goal 19 in Brazil through the legal provisions of the Brazilian federated entities, showed us many contradictions and the prevalence of managerial logic in the analyzed legislation. Regarding the goal of democratic school management in the Plans, it appears that the majority adhered to goal 19 of the National Education Plan. However, this adherence associated with “merit and performance” criteria, even considering the “public consultation” of the school community, compromises the effectiveness of democratic school management - GDE, given that the aspects highlighted by the Plans are directly linked to a managerial and meritocratic management . Only twelve federated entities have specific GDE laws, in which we perceive similarities between the legal pieces, even though the federated entities present different ways of how they will effect democratic management in their education systems. It is concluded that, in the totality of the Plans and of the analyzed laws, we consider that the regulation of the democratic school management in our country, still happens in an incipient way in all the Brazilian regions.